2014
DOI: 10.1016/b978-0-444-53685-3.00013-1
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity and Ambiguity Aversion

Abstract: The phenomena of ambiguity and ambiguity aversion, introduced in Daniel Ellsberg's seminal 1961 article, are ubiquitous in the real-world and violate both the key rationality axioms and classic models of choice under uncertainty. In particular, they violate the hypothesis that individuals' uncertain beliefs can be represented by subjective probabilities (sometimes called personal probabilities or priors). This chapter begins with a review of early notions of subjective probability and Leonard Savage's joint ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(92 citation statements)
references
References 189 publications
(176 reference statements)
9
82
0
1
Order By: Relevance
“…In our approach, ambiguity aversion is only one of the conceptual landscapes surrounding the decision-maker's choice in a situation where ambiguity is present (Aerts et al, 2014). This representation is compatible with the experimental findings confirming Ellsberg's prediction about the human attitude toward ambiguity, but also with some recent experiments where such attitude is more controversial (see, e.g., Binmore, Stewart, & Voorhoeve, 2012;Slovic & Tversky, 1974); see also the review (Machina & Siniscalchi, 2014).…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our approach, ambiguity aversion is only one of the conceptual landscapes surrounding the decision-maker's choice in a situation where ambiguity is present (Aerts et al, 2014). This representation is compatible with the experimental findings confirming Ellsberg's prediction about the human attitude toward ambiguity, but also with some recent experiments where such attitude is more controversial (see, e.g., Binmore, Stewart, & Voorhoeve, 2012;Slovic & Tversky, 1974); see also the review (Machina & Siniscalchi, 2014).…”
Section: Introductionsupporting
confidence: 83%
“…People prefer the unambiguous act over its ambiguous counterpart. There is a huge experimental evidence that decision-makers actually show this ambiguity aversion (see, e.g., the extensive review by Machina & Siniscalchi, 2014). Only the experiment by Slovic and Tversky (1974) indicated that 'ambiguity attraction' was at play, while more recent experiments identify other behavioral mechanisms as primary (Binmore et al, 2012).…”
Section: Actmentioning
confidence: 95%
See 1 more Smart Citation
“…They consider both the Savage setting, with acts mapping to prizes, and the horse-roulette act framework, with acts mapping to objective probability distributions over prizes, and restrict their attention to preferences that admit a Choquet Expected Utility representation on binary acts, but are otherwise arbitrary. For a comprehensive review of the notion of ambiguity aversion, we refer the reader to Machina and Siniscalchi (2014). 9.2 Ambiguity aversion and portfolio choice Keynes (1921) was perhaps the first economist to grasp the full significance of uncertainty for economic analysis and portfolio choice. Whereas conventional models of choice under risk promote diversification, Keynes expressed the view that one should allocate wealth in the few stocks about which one feels most favorably.…”
Section: Schmeidler's Uncertainty Aversionmentioning
confidence: 99%
“…Machina and Siniscalchi 2014). The first is full Bayesian updating with a simple interpretation for multiple prior models: all priors in the relevant set are updated prior-by-prior according to Bayes rule.…”
Section: Introductionmentioning
confidence: 99%